2007
DOI: 10.1007/s10562-007-9080-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of La on Au-ceria catalyst for water gas shift reaction

Abstract: For Au-ceria catalysts prepared by deposition-precipitation method, catalytic performance of water gas shift reaction was studied in different La loadings. In the complete doping range, ceria retains with its cubic fluorite structures. BET, XRD, H 2 -TPR, HRTEM studies showed that La doping can improve the activity of Au-ceria catalyst by stabilizing ceria and modifying its morphology. In addition, the test of catalyst stability evaluation also proved a better stability performance of Au-ceria catalyst can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…That is to say, it could be reasonable to assume that the hydrogen consumption is determined by the reduction extent of ceria for the catalysts. From Table 3, hydrogen consumption of La doping catalysts is much higher than that of Ru/CeO 2 , indicating that La doping could promote the reduction of ceria, which is good accordance with the predecessors' studies [17]. Figure 6 represent the XPS spectra of Ru/CeO 2 and Ru/ CeO 2 -10La catalysts at Ce 3d.…”
Section: H 2 -Tpr and H 2 -Tpdsupporting
confidence: 81%
See 2 more Smart Citations
“…That is to say, it could be reasonable to assume that the hydrogen consumption is determined by the reduction extent of ceria for the catalysts. From Table 3, hydrogen consumption of La doping catalysts is much higher than that of Ru/CeO 2 , indicating that La doping could promote the reduction of ceria, which is good accordance with the predecessors' studies [17]. Figure 6 represent the XPS spectra of Ru/CeO 2 and Ru/ CeO 2 -10La catalysts at Ce 3d.…”
Section: H 2 -Tpr and H 2 -Tpdsupporting
confidence: 81%
“…CeO 2 and La doping CeO 2 have two peaks at 200-400 and 400-650°C from ambient temperature to 750°C, respectively. These peaks usually were assigned to the reduction of the surface oxygen and sub-surface oxygen of ceria and mixed oxides [17].…”
Section: H 2 -Tpr and H 2 -Tpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereinto, many scientists have paid attention to the ceria loaded with precious metals (Pt, Pd and Rh) [6][7][8], especially gold [9][10][11]. The effect of La as additive on the catalytic performance of Au-ceria WGS catalyst was then studied by our group [12]. However, due to the high cost of the above precious metals and/or their instability, more and more attention has been focused on the cheap transition metals, especially the ceria-supported copper catalysts that have been found to show high catalytic activity for the WGS reaction and are expected to substitute for the noble metal catalysts in the future [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…3a shows the TPR profile of the CeO 2 , Ce 4 La, Ce 8 La and Ce 12 La supports, where it can be observed that the reduction peak located at 550 • C in CeO 2 (peak related to surface-capping oxygen of CeO 2 ) is shifted to lower temperature, after addition of La 2 O 3 . This finding suggests that this displacement is due to the solid solution Ce(La)O x formed [58,61,28].…”
Section: Characterizationmentioning
confidence: 90%